Volkserzählungen der Südslaven Märchen und Sagen, Schwänke, Schnurren und erbauliche Geschichten. - Krauss, Friedrich Salomo (2002)
The hitherto unpublished collection of South Slavic folk tales in German translation in the legacy of Friedrich Salomo Krauss (1859-1938), jewish-croatian ethnography, writer and sexologist, in Los Angeles, is on the one hand based on field-work materials, collected from oral sources during a research excursion in 1884-5 in Bosnia, Hercegovina and Dalmatia, on the other on translations of stories published in South Slavic journals of folklore and collections of oral narrations round the turn of the century of 1900. The translations are done in a literary style and the partly extended commentaries by Krauss are an important document of Viennese culture history and mentality in the first decades of the 20th century. Moreover, this collection documents the different ideological presuppositions for the starting phase of the emergence of Austrian Volkskunde/ethnography, which was from the very beginning internationally orientated, in close and specific connection to the folk culture of the countries in South Eastern Europe, and cultivated in a multidisciplinary way cross-contacts to ethnology, anthropology, psychology and jurisprudence.